A conceptual framework for the analysis of the effect of institutions on biofuel supply chains. (1st January 2017) - Moncada, J.A.; Lukszo, Z.; Junginger, M.; Faaij, A.; Weijnen, M.
Highlights: Proposes a conceptual framework to analyze biofuel supply chains. The German biodiesel supply chain was formalized into an agent-based model. Patterns in production capacity result from investors' perceptions of the market. This methodology could be used to analyze different deployment strategies. Abstract: The economic performance of biofuels supply chains depends on the interaction of technical characteristics as technological pathways and logistics, and social structures as actor behavior, their interactions and institutions. Traditional approaches focus on the technical problems only. Little attention has been paid to the institutional analysis of biofuel supply chains. This paper aims to extend the analysis of the effect of institutions on the emergence of biofuel supply chains by developing a conceptual framework that combines elements of complex adaptive systems, (neo) institutional economics and socio-technical systems theory. These elements were formalized into an agent-based model. The proposed method is illustrated by a case study on a biodiesel supply chain in Germany. It was found that the patterns in production capacity result from investors basing their decisions on optimistic perceptions of the market development that increase with a favorable institutional framework. Conversely, patterns in biodiesel production cannot be completely explained by this mechanism. The proposed framework assisted the model conceptualization phase and allowed the incorporation of social structures into the agent-based model. This approach could be developed further to provide insights on the effect of different future deployment strategies on bioenergy systems emergence and development.